THE EFFECT OF ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) ON CORPORATE PERFORMANCE WITH ENTERPRISE RISK MANAGEMENT (ERM) AS A MEDIATING VARIABLE - Nur Azizah; Suwarno Suwarno (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
This research association the correlation between ESG and corporate performance, with ERM as an intervening variable among manufacturing companies listed on the Indonesia Stock Exchange during the 2022–2024 period. Using a quantitative research design and secondary data obtained from firms’ published reports, the empirical results show that ESG initiatives do not exert a direct impact on firm performance. Moreover, ESG is found to have a negative and statistically significant relationship with ERM, indicating that ESG implementation may function as an alternative mechanism for addressing non-financial risk exposures. The analysis further reveals that ERM neither significantly influences corporate performance nor mediates the relationship between ESG and performance. Interpreted through the lens of stakeholder theory, these results suggest that the performance implications of ESG and ERM are not immediate but are shaped by firm-specific characteristics and contextual conditions. Overall, the findings highlight the inherent complexity of aligning sustainability strategies with risk management practices to enhance firm performance in emerging market settings. Keywords: ESG, ERM, Corporate Performance, Stakeholder Theory